Raf-induced proliferation or cell cycle arrest is determined by the level of Raf activity with arrest mediated by p21Cip1. - Woods, D (1997)
The Raf family of protein kinases display differences in their abilities to promote the entry of quiescent NIH 3T3 cells into the S phase of the cell cycle. Although conditional activation of deltaA-Raf:ER promoted cell cycle progression, activation of deltaRaf-1:ER and deltaB-Raf:ER elicited a G1 arrest that was not overcome by exogenously added growth factors. Activation of all three deltaRaf:ER kinases led to elevated expression of cyclin D1 and cyclin E and reduced expression of p27Kip1. However, activation of deltaB-Raf:ER and deltaRaf-1:ER induced the expression of p21Cip1, whereas activation of deltaA-Raf:ER did not. A catalytically potentiated form of deltaA-Raf:ER, generated by point mutation, strongly induced p21Cip1 expression and elicited cell cycle arrest similarly to deltaB-Raf:ER and deltaRaf-1:ER. These data suggested that the strength and duration of signaling by Raf kinases might influence the biological outcome of activation of this pathway. By titration of deltaB-Raf:ER activity we demonstrated that low levels of Raf activity led to activation of cyclin D1-cdk4 and cyclin E-cdk2 complexes and to cell cycle progression whereas higher Raf activity elicited cell cycle arrest correlating with p21Cip1 induction and inhibition of cyclin-cdk activity. Using green fluorescent protein-tagged forms of deltaRaf-1:ER in primary mouse embryo fibroblasts (MEFs) we demonstrated that p21Cip1 was induced by Raf in a p53-independent manner, leading to cell cycle arrest. By contrast, activation of Raf in p21Cip1(-/-) MEFs led to a robust mitogenic response that was similar to that observed in response to platelet-derived growth factor. These data indicate that, depending on the level of kinase activity, Raf can elicit either cell cycle progression or cell cycle arrest in mouse fibroblasts. The ability of Raf to elicit cell cycle arrest is strongly associated with its ability to induce the expression of the cyclin-dependent kinase inhibitor p21Cip1 in a manner that bears analogy to alpha-factor arrest in Saccharomyces cerevisiae. These data are consistent with a role for Raf kinases in both proliferation and differentiation of mammalian cells.